Experience and Insight Author in Preventing and Curbing the Novel Coronavirus (Covid19) Outbreak - Rahmidha Dwijayanti (Universitas Airlangga, 2020)
Introduction: In December 31, 2019, China gave bad news the World Health Organization (WHO) throughtout an outbreak of a mysterious pneumonia characteristic in Wuhan, which is located in Hubei Province with 11 million people. On 1 January 2020, the source of the Coronavirus outbreak is a seafood market that has been closed. The Huanan Seafood Wholesale Market in Wuhan City, where the virus was first detected, fit that description to a tee, with vendors illegally trading in wild and exotic animals alongside the daily ocean catch. Discussion: This literature review retrieved the articles from databases such as Springer, PubMed, and Google Scholar. The articles on preventing were 17 articles and curbing were 15 articles. The literatur review is a critical and in-depth evaluation of previous research to obtain important information about the dangers of the corona virus and the important of preventing and curbing the corona virus. Guidance regarding personal protective equipment in infection prevention and control is provided by WHO. Goggles and face shield must always be used to protect against potential hazards, and health workers don't touch mucous membranes (eyes, nose or mouth). Conclusion: Recommendations for preventing health and preventing Covid19 are: limiting physical contact or being in a room with people without symptoms, covering the mouth with a tissue when sneezing or coughing and then throwing the tissue into the trash. If there are no tissues, use your sleeves to avoid liquids or droplets on other people or sticking to nearby objects, do not travel to the red zone against the spread of Covid19, rub hands properly for 20 seconds with soap and water, If it is quite difficult to find water, it is advisable to always have a Hand Sanitizer with an alcohol content of at least 60% which is believed to be able to kill germs. Recommendation for curbing the spread the Covid19 include: lockdown, stay at home, and physical inactivity.